Uniconazole-mediated growth regulation in Ophiopogon japonicus: yield maximization vs. medicinal quality trade-offs - Cai, Xiaoyang; Li, Wenjing; Fan, Heling; Zhang, Jiaming; Wang, Haohan; Qing, Yan; Li, Min; Gou, Yan (Frontiers in Plant Science, 2025)
IntroductionOphiopogon japonicus (L. f.) Ker-Gawl., commonly known for its tuberous roots, is a renowned medicinal plant widely used in traditional medical systems across China, Japan, and parts of Southeast Asia. In China in particular, Ophiopogonis Radix has been employed for thousands of years as both a herbal remedy and a health-promoting food, embodying a long-standing tradition of dual medicinal and dietary use. Based on geographic origin, it is typically classified into two main types: “Chuanmaidong” (CMD) from Sichuan and “Zhemaidong” (ZMD) from Zhejiang. This study investigates the impact of foliar-applied Uniconazole, a triazole-based plant growth regulator, on the agronomic traits and medicinal quality of Ophiopogon japonicus (cv. Chuanmaidong No.1) under field conditions in Sichuan, China. The research addresses a critical question in medicinal plant cultivation: can yield enhancement via plant growth regulators be achieved without compromising pharmacological quality?MethodsUniconazole was applied at rates ranging from 7.5, 15, and 30 kg/hm². Plant morphological traits, tuber yield components, bioactive compound contents, and environmental residues were systematically evaluated. Hormonal profiling and degradation kinetics were also assessed to elucidate physiological mechanisms and ecological safety.ResultsUniconazole application inhibited vegetative growth, reducing plant height and leaf biomass. However, it markedly increased tuber yield—by up to 101.59%—through hormone-mediated morphological remodeling. This was driven by disruptions in endogenous hormone homeostasis, particularly in Abscisic Acid (ABA) - Gibberellic acid 3 (GA3) balance and Indole-3-Acetic Acid (IAA) - Zeatin Riboside (ZR) coordination, promoting the transformation of root shapes from standard spindle forms to cylindrical or dumbbell types. Dimensional traits improved significantly: root diameter increased by 12.36%, length by 21.75%, and single tuber dry weight by 49.53%. Despite modest increases in polysaccharide and flavonoid levels, total saponins and ophiopogonin D—key pharmacologically active compounds—declined by 35.90% and 63.94%, respectively. Environmental residue analysis showed first-order degradation kinetics, with half-lives of approximately 19.7 days in both soil and root tissue, and final residues falling below detection thresholds.ConclusionWhile Uniconazole enhances short-term economic returns through yield amplification, it poses substantial challenges to medicinal quality and regulatory compliance. The induced morphological deviations complicate adherence to Chinese Pharmacopoeia identification standards and may increase adulteration risks. Most concerning is the sharp reduction in saponins, which undermines clinical efficacy and pharmaceutical processing. This study calls for urgent policy reforms, including mandatory quantification of bioactive markers and routine residue monitoring, to safeguard the integrity of medicinal plant supply chains. A balanced cultivation paradigm is essential—one that reconciles agricultural intensification with the core therapeutic values of medicinal crops: efficacy, safety, and authenticity.